Should We Use the IMPACT-Model for the Outcome Prognostication of TBI Patients? A Qualitative Study Assessing Physicians' Perceptions. Issue 1 (March 2018) - Moskowitz, Jesse; Quinn, Thomas; Khan, Muhammad W.; Shutter, Lori; Goldberg, Robert; Col, Nananda; Mazor, Kathleen M.; Muehlschlegel, Susanne
Introduction. Shared Decision-Making may facilitate information exchange, deliberation, and effective decision-making, but no decision aids currently exist for difficult decisions in neurocritical care patients. The International Patient Decision Aid Standards, a framework for the creation of high-quality decision aids (DA), recommends the presentation of numeric outcome and risk estimates. Efforts are underway to create a goals-of-care DA in critically-ill traumatic brain injury (ciTBI) patients. To inform its content, we examined physicians' perceptions, and use of the IMPACT-model, the most widely validated ciTBI outcome model, and explored physicians' preferences for communicating prognostic information towards families.Methods. We conducted a qualitative study using semi-structured interviews in 20 attending physicians (neurosurgery, neurocritical care, trauma, palliative care) at 7 U.S. academic medical centers. We used performed qualitative content analysis of transcribed interviews to identify major themes.Results. Only 12 physicians (60%) expressed awareness of the IMPACT-model; two stated that they "barely" knew the model. Seven physicians indicated using the model at least some of the time in clinical practice, although none used it exclusively to derive a patient's prognosis. Four major themes emerged: the IMPACT-model is intended for research but should not be applied to individual patients; mistrust in the IMPACT-model derivation data; the IMPACT-model is helpful in reducing prognostic variability among physicians; concern that statistical models may mislead families about a patient's prognosis.Discussion: Our study identified significant variability of the awareness, perception, and use of the IMPACT-model among physicians. While many physicians prefer to avoid conveying numeric prognostic estimates with families using the IMPACT-model, several physicians thought that they "ground" them and reduce prognostic variability among physicians. These findings may factor into the creation and implementation of future ciTBI-related DAs.